Komunikasi Antarbudaya Mahasiswa Indonesia pada Program Summer Course di Thailand - Muhammad Rangga Pratama; Andalusia Neneng Permatasari (Bandung Conference Series: Communication Management, 2024)
Abstract. This research is motivated by the activities of the Summer Course program of Indonesian students in Thailand. As social beings, we must know the importance of intercultural communication that must be done to create harmony and togetherness. Differences in culture, language and culture become a problem faced when entering a new environment. Intercultural communication is communication that occurs between people who have different cultural backgrounds. This research will focus on Indonesian students who carry out IC-RMUTK Summer Course program activities. This research uses qualitative research methods with a phenomenological study approach that uses interview techniques, observation, and documentation. Data analysis techniques, data reduction, data presentation, conclusion drawing. The result of this research is the meaning of Indonesian students in intercultural communication in Summer Course activities in Thailand has the motive of learning experience abroad, and getting the conversion value of the course. Then, the experience and adaptation gained communicating with Thai students using foreign languages in the context of Thai culture. Abstrak. Penelitian ini dilatar belakangi dari kegiatan program Summer Course mahasiswa Indonesia di Thailand. Sebagai makhluk sosial, kita harus mengetahui pentingnya komunikasi antar budaya yang harus dilakukan untuk menciptakan keselarasan dan kebersamaan. Perbedan kultur, bahasa dan budaya menjadi sebuah permasalahan yang dihadapi jika masuk ke lingkungan yang baru. komunikasi antarbudaya adalah komunikasi yang terjadi antara orang-orang yang memiliki latar belakang kebudayaan yang berbeda satu sama lain. Penelitian ini akan difokuskan kepada mahasiswa Indonesia yang melaksanakan kegiatan program Summer Course IC-RMUTK. Dalam penelitian ini menggunakan metode penelitian kualitatif dengan pendekatan studi fenomenologi yang menggunakan teknik wawancara, observasi, dan dokumentasi. Teknik analisis data, Reduksi Data, Penyajian Data, Penarikan Kesimpulan. Hasil dari penelitian ini adalah pemaknaan mahasiswa Indonesia dalam komunikasi antarbudaya pada kegiatan Summer Course di Thailand memiliki motif pengalaman belajar di luar negeri,dan mendapatkan nilai konversi mata kuliah. Kemudian, pengalaman dan adaptasi yang diperoleh berkomunikasi dengan mahasiswa Thailand menggunakan bahasa asing dalam konteks kebudayaan Thailand.